2012
DOI: 10.1603/ec11163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Heavy Metal Cu<SUP>2+</SUP> on Growth, Development, and Population Dynamics of Spodoptera litura (Lepidoptera: Noctuidae)

Abstract: Spodoptera litura (F.) larvae were fed with artificial food containing four different concentrations of copper (25, 50, 100, and 200 mg/kg). Copper affected growth, development, and population dynamics of late instar larvae. Our results indicate that the fourth and fifth instar survival rates were significantly reduced at 50-200 mg/kg copper (Cu2+). Moreover, all the Cu2+ treatments significantly reduced pupation and moth emergence rates in a dose-dependent manner. Larvae fed 25 or 50 mg/kg Cu2+ showed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The concentrations of nickel and copper in leaves of different plants growing in the most polluted sites near the Monchegorck smelter reached 500-800 µg g −1 [17,35]. The earlier experiments demonstrated that 50-200 µg g −1 of copper added to the larval diet decreased the pupal weight of the oriental leafworm moth, Spodoptera litura (F.), to 80% of the control value [39], whereas 100 µg g −1 of nickel did not affect wing size in the cabbage white butterfly, Pieris rapae (L.) [40]. At the same time, the wing length of the autumnal moth Epirrita autumnata (Bkh.)…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of nickel and copper in leaves of different plants growing in the most polluted sites near the Monchegorck smelter reached 500-800 µg g −1 [17,35]. The earlier experiments demonstrated that 50-200 µg g −1 of copper added to the larval diet decreased the pupal weight of the oriental leafworm moth, Spodoptera litura (F.), to 80% of the control value [39], whereas 100 µg g −1 of nickel did not affect wing size in the cabbage white butterfly, Pieris rapae (L.) [40]. At the same time, the wing length of the autumnal moth Epirrita autumnata (Bkh.)…”
Section: Discussionmentioning
confidence: 99%
“…Cations such as Ca 2+ , Mg 2+ , Fe 2+ , Cu 2+ , and Zn 2+ are essential components for the appropriate functioning of some enzymes but may be toxic to the insect in high amounts (Lu, Di, & Xueping, ; Zan, Yang, & Wang, ). Huang, Kong, and Seng () demonstrated that low concentrations of metal ions favor the development of Spodoptera litura (Lepidoptera: Noctuidae) in the first larval instars, but a “delayed effect” causes these metals to be harmful in the last instars, leading to a decrease in larval time and increased mortality. Huang et al () also suggest that a concentration of up to 50 mg kg −1 of Cu 2+ in the diet of S. litura favors the development of the caterpillar between the first and third instars.…”
Section: Resultsmentioning
confidence: 99%
“…Huang, Kong, and Seng () demonstrated that low concentrations of metal ions favor the development of Spodoptera litura (Lepidoptera: Noctuidae) in the first larval instars, but a “delayed effect” causes these metals to be harmful in the last instars, leading to a decrease in larval time and increased mortality. Huang et al () also suggest that a concentration of up to 50 mg kg −1 of Cu 2+ in the diet of S. litura favors the development of the caterpillar between the first and third instars. Values above 50 mg kg −1 would have a cumulative effect on the insect, especially in the later instars, leading to death.…”
Section: Resultsmentioning
confidence: 99%
“…Data are shown in Table (2) indicated that the adult mortality percentage was estimated from 1 to 7 days after treatment to be 13.3and 35.3 % when adult fed on Magnetic Seawater with traces of mixture (2.5g/l) of ferro-salts mixture 1:1, respectively, and increased to 73.3 and 59.3 % in case of treating the adults with the 3 rd group fed on Magnetic Seawater with traces of mixture (50g/L) of ferrosalts mixture 1:1 and match, respectively, (Fig.1,c). Huang et al (2012) demonstrated that lower concentrations of Cu in the diet (25 and 50 mg/kg) shorten the generation time by 4-5 days, while higher concentrations (100 and 200 mg/kg) increased the duration by 1-2 days. Cu, Fe, and Zn are considered as important and essential elements of nutrition for the organisms.…”
Section: Adult Mortality Percentagementioning
confidence: 98%
“…But some authors effect of some menials on many insects such as; Zinc and copper connect to the cytosol metallothionein in the midgut of many organisms, but at high concentrations could be toxic (Jensen and Trumble, 2003) also, (Sun et al 2011) recorded that the effect of a high concentration of nickel in Spodoptera litura Fabricus reduced IGR but a low concentration of nickel increased IGR. (Huang et al 2012 and). Baghban, et al 2014) Studied the effects of the heavy metal Cu2+ and Cd, Cu, and Zn on growth, development, and population dynamics of Spodoptera litura and Helicoverpa armigera (Lepidoptera: Noctuidae…”
Section: Introductionmentioning
confidence: 99%